Collaborative Governance Strategy in Increasing Production and Strengthening Food Diversification in Rokan Hulu Regency, Riau Province, Indonesia - Yusri, Ali; Fadli, Mashur; Pane, Rico Purnawandi; Rafi, M; Wasillah, Asiah; Zebua, Ben Hansel Notatema; Alby, Syahroni (Universitas Muhammadiyah Yogyakarta, 2024)
This research aims to analyze Collaborative Governance strategies in food diversification efforts in Rokan Hulu Regency, focusing on the regional food policy context. Utilizing qualitative analysis with the Nvivo 12 Plus tool, it systematically processes interview and online media data, revealing key factors such as coordination (47.06%), trust (29.41%), and commitment to common goals (23.53%) that influence collaborative governance. The novelty lies in highlighting the low level of stakeholder commitment, linked to a lack of participation forums, which impacts local food consumption patterns still dependent on rice. While leadership and institutional design are identified as critical aspects of collaborative governance, this study advances the discourse by emphasizing the dominance of the government sector and the need for more balanced stakeholder involvement in program implementation. It also underscores the importance of developing alternative commodities like corn and cassava to enhance food diversification. This research contributes to the state of the art by offering timely insights into the practical challenges of collaboration, advancing both theoretical and applied aspects of governance in rural food security strategies.